2022
DOI: 10.3390/app12042213
|View full text |Cite
|
Sign up to set email alerts
|

Spray Drying and Spout-Fluid Bed Drying Microencapsulation of Mexican Plum Fruit (Spondias purpurea L.) Extract and Its Effect on In Vitro Gastrointestinal Bioaccessibility

Abstract: The Mexican plum (Spondias purpurea L.) is a source of phenolic compounds; however, these compounds are susceptible to various factors (humidity, temperature, light, oxygen), as well as the digestion process, which can modify their bioaccessibility. This study aimed to extract and microencapsulate the phenolic compounds (PC), total anthocyanins (TA), ascorbic acid (AA), dehydroascorbic acid (DHA) and total vitamin C (AA+DHA) from Mexican plum ecotype “Cuernavaqueña” by spray drying (SD) and spout-fluid bed dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
3
6
0
Order By: Relevance
“…No significant difference (p < 0.05) was observed. These results agreed with other studies [7,9] and the moisture content of the powders obtained is typical for spray dried products. Studies have reported that values between 1 and 6% are desirable to preserve the stability of microcapsules during their storage [28].…”
Section: Moisture Content and Water Activity (Aw)supporting
confidence: 93%
See 2 more Smart Citations
“…No significant difference (p < 0.05) was observed. These results agreed with other studies [7,9] and the moisture content of the powders obtained is typical for spray dried products. Studies have reported that values between 1 and 6% are desirable to preserve the stability of microcapsules during their storage [28].…”
Section: Moisture Content and Water Activity (Aw)supporting
confidence: 93%
“…No significant difference (p < 0.05) was observed. These results agreed with other studies [7,9]. Several authors have reported that a w values below 0.6 indicate stability of a food product because of the low amount of free water available for biochemical reactions [29].…”
Section: Moisture Content and Water Activity (A W )supporting
confidence: 92%
See 1 more Smart Citation
“…A commonly used one is maltodextrin. Aguilera‐Chávez et al (2022) studied fluid bed coating encapsulation of Mexican plum powder and showed better retention of bioactive compounds. Microcapsules of fluid bed coating encapsulation higher retention efficiency of phenolic compounds than the spray drying process of encapsulation.…”
Section: Encapsulating Techniquesmentioning
confidence: 99%
“…Many factors affect the quality of microcapsules, including the preparation technique and the type of coating material [ 17 ]. Fluidized bed microencapsulation is the prevalent approach and offers several advantages, including low cost, minimal dust pollution, high uniformity, high encapsulation efficiency, and excellent stability [ 18 , 19 ]. The polymer utilized further enhances the quality and stability of the microencapsulation; hence, choosing the proper base polymer should be performed [ 17 , 20 ].…”
Section: Introductionmentioning
confidence: 99%